2022
DOI: 10.5032/jae.2022.03216
|View full text |Cite
|
Sign up to set email alerts
|

When Teaching Hurts: Exploring the Secondary Traumatic Stress Experiences of Early-Career SBAE Teachers

Kirby J. Schmidt,
D. Brett Milliken,
Amy M. González Morales
et al.

Abstract: Sources of satisfaction, stress, and burnout are all-too-familiar to school-based agricultural education (SBAE) teachers. Yet, the current literature related to SBAE stress has not addressed the overwhelming existence of trauma in our greater society. Teacher wellbeing can be compromised when students share their own adversities and traumatic experiences, thus producing secondary traumatic stress (STS). To lay a foundation for inquiry, we used the Professional Quality of Life (ProQOL) survey and scale to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…3). As a result, agricultural educators are often more aware of students' experiences outside of the classroom (Schmidt et al, 2022). According to Hainline et al (2015), agricultural educators reported working 58.65 hours per week, many of which are through supporting SAE project development and travel associated with contests or conferences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3). As a result, agricultural educators are often more aware of students' experiences outside of the classroom (Schmidt et al, 2022). According to Hainline et al (2015), agricultural educators reported working 58.65 hours per week, many of which are through supporting SAE project development and travel associated with contests or conferences.…”
Section: Discussionmentioning
confidence: 99%
“…These five central principles guide how the CTT informs educators and mental health practitioners on how to approach healing. The agricultural educators' unique positioning to emotionally support students struggling with childhood trauma (Schmidt et al, 2022) can be a vessel for the CTT. Engaging the CTT, alongside the WSCC and TIC models, can provide an avenue for educators to leverage teacher-student relationships for emotional guidance and assist in the development of the resiliency and coping skills necessary to mitigate the negative effects of childhood trauma.…”
Section: Reenactmentmentioning
confidence: 99%
See 3 more Smart Citations